PKC Activation is Required for TSH-mediated Lipolysis via Perilipin Activation - Thrush, A. B.; Gagnon, A.; Sorisky, A. (Hormone and Metabolic Research, 2012)
Adipocytes express TSH receptors, and TSH can stimulate cAMP-dependent protein kinase, perilipin phosphorylation, and lipolysis in human and mouse 3T3-L1 adipocytes. TSH activates PKC in thyrocytes. Since PKC has been implicated in lipolysis in adipocytes, we examined whether the family of conventional isoforms of PKC (cPKC) is a target of TSH in adipocytes, and whether cPKC is required for TSH-stimulated lipolysis. Differentiated 3T3-L1 and subcutaneous abdominal human adipocytes in culture were treated with TSH in the presence or absence of either PKC inhibitor Gö6976 (inhibits PKCα, βI) or Gö6983 (inhibits PKCα, βI, βII, γ, δ). Activation of cPKC was assessed by phospho-(ser) PKC substrate antibody immunoblot analysis. Perilipin phosphorylation was measured by SDS-PAGE electromobility shift followed by anti-perilipin immunoblot analysis. Lipolysis was quantified by the amount of nonesterified fatty acids (NEFAs) released into the medium. TSH strongly and significantly activated cPKC in differentiated human and 3T3-L1 adipocytes from undetectable levels in control conditions. This cPKC stimulation in human adipocytes by TSH was reduced significantly by 40% or 48% in the presence of PKC inhibitor Gö6983 or Gö6976, respectively. Gö6976 inhibited TSH-stimulated human adipocyte perilipin phosphorylation and NEFA release by 80% and 50%, respectively. We conclude that cPKC is activated by TSH in human differentiated adipocytes. Based on the effects of cPKC inhibition, cPKC activation is required for TSH-stimulated perilipin phosphorylation and lipolysis in human differentiated adipocytes.
Keywords: nonesterified fatty acids; subclinical hypothyroidism; 3T3-L1